1987
DOI: 10.1002/aic.690331104
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the heat integration of chemical process plants

Abstract: A method for solving the problem of heat exchanger network synthesis in chemical process plants is presented based on the use of the outof-kilter algorithm. The method represents an extension of previous approaches based on network flow problem formulations. A new approach to overcome the constraints in forbidden-match problems, termed the dual stream approach, has been developed based on the use of a stream as both a hot and a cold stream. This approach results in considerable savings in utility costs in cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Our solution involved the concept of hot-to-hot and cold-to-cold matches (heat exchange between streams of the same type). Such solutions were apparently first proposed on heuristic grounds by Grimes et al (1 982) and have since been found algorithmically by us and by Viswanathan and Evans (1987), who refer to such matches as dual stream solutions, since a hot or cold stream plays a role of both a hot and a cold stream in different parts of the network.…”
Section: 'Grand Canonical' Optimization: Heat Exchanger Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Our solution involved the concept of hot-to-hot and cold-to-cold matches (heat exchange between streams of the same type). Such solutions were apparently first proposed on heuristic grounds by Grimes et al (1 982) and have since been found algorithmically by us and by Viswanathan and Evans (1987), who refer to such matches as dual stream solutions, since a hot or cold stream plays a role of both a hot and a cold stream in different parts of the network.…”
Section: 'Grand Canonical' Optimization: Heat Exchanger Networkmentioning
confidence: 99%
“…Capital investment is clearly greater using this approach since a single exchanger in the constraint-free MER design is replaced by two exchangers and the additional piping necessary for the intermediate stream. By using hot-to-hot and cold-to-cold matches, the designs found algorithmically for forbidden match problems by GCSA and by the method of Viswanathan and Evans (1987) circumvent the need for intermediate streams, essentially by using existing process streams for the same purpose.…”
Section: 'Grand Canonical' Optimization: Heat Exchanger Networkmentioning
confidence: 99%
“…Furthermore, heat exchange is not permitted between streams of same type (hotehot/coldecold). However, it has been proven that the utility requirement can also be reduced by such forbidden matches from several former works [36,37,41], which may reduce the TAC simultaneously. In a recent work, Pariyani et al [28] proposed a randomized algorithm to generate networks by random sampling with a series of structure and thermodynamics bounds, which permits to arrange utilities not only at the end of each stream.…”
Section: Hen Structure Representationmentioning
confidence: 95%
“…From Dolan et al (1987) and Wiswanathan and Evans (1987) the utility requirement can be reduced in a forbidden-match problem. The method consists of matching one of the streams (hot/cold) of the forbidden match with another same stream (hot/cold) by utilizing the heat content of the second stream; as a result, the utility consumption could be considerably reduced.…”
Section: Problem Statementmentioning
confidence: 96%